Striatal direct and indirect pathways control decision-making behavior - Macpherson, Tom; Morita, Makiko; Hikida, Takatoshi (Frontiers in Psychology, 2014)
Despite our ever-changing environment, animals are remarkable adept at selecting courses of action that are predictive of optimal outcomes. While requiring the contribution of a number of brain regions, a vast body of evidence implicates striatal mechanisms of associative learning and action selection to be critical to this ability. While numerous models of striatal-based decision-making have been developed, it is only recently that we have begun to understand the precise contributions of specific subpopulations of striatal neurons. Studies utilizing contemporary cell-type-specific technologies indicate that striatal output pathways play distinct roles in controlling goal-directed and social behaviors. Here we review current models of striatal-based decision-making, discuss recent developments in defining the functional roles of striatal output pathways, and assess how striatal dysfunction may contribute to the etiology of various neuropathologies.